Analisis Kemampuan Pemecahan Masalah Matematika ditinjau dari Tipe Kepribadian Siswa Madrasah Tsanawiyah - Mariya Sulastri; Laila Hayati; Nurul Hikmah; Syahrul Azmi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to describe the mathematical problem solving abilities in terms of students personality types of grade VIII at MTs Al-Ma’arif NU Qamarul Huda Narmada academic year 2020/2021. This type of research is a qualitative descriptive with a quantitative approach. The sampling technique used saturated sampling and each 2 students were selected to represent each personality types. The data collection technique used are personality type questionnaires, mathematical problem solving ability tests, and interviews. The data analysis techniques used quantitative data analysis and qualitative data analysis that are data reduction, data presentation and conclusions. The result of this study are students with introvert and extrovert personality types are not able to write down the stage of understanding the problem, do the stage of making a plan by writing them into mathematical form, able to write down the problem solving systemtatically but there are some errors, write the conclusion of the answer though it’s not quite right. While students with ambivert personality types are able to do the stage of understanding the problem by writing down even though it’s incomplete, write a plan for solving the problem by directly writing it into mathematical form, are able to write the solution of the problem according to the plan even though there are some missteps, re-examine and write down the conclusion even though there are error in the results.